Self-Rectified Graphite-Based Reprogrammable One-Time Programmable (RS-OTP) Memory for Embedded Applications - Chen, Ying-Chen (Frontiers in Nanotechnology, 2021)
A graphite-based RRAM device with self-rectifying characteristic named “nonlinearity (NL)” is developed for high density crossbar array for in-memory computing with low power and high scalability. Meanwhile, the reprogrammable functions is presented in self-selected RRAM as a promising candidate for one-time-programmable (OTP) in the emerging memory embedded applications, such as security, system-on-chip (SoC), and internet-of-things (IoT).